Epigenetic modifications induced by exercise: Drug-free intervention to improve cognitive deficits associated with obesity - Barros, Leonardo; Eichwald, Tuany; Solano, Alexandre Francisco; Scheffer, Débora; da Silva, Rodrigo Augusto [UNESP]; Gaspar, Joana M.; Latini, Alexandra (Elsevier, 2019)
Obesity and metabolic disorders are increasing worldwide and are associated with brain atrophy and dysfunction, which are risk factors for late-onset dementia and Alzheimer's disease. Epidemiological studies demonstrated that changes in lifestyle, including the frequent practice of physical exercise are able to prevent and treat not only obesity/metabolic disorders, but also to improve cognitive function and dementia. Several biochemical pathways and epigenetic mechanisms have been proposed to understand the beneficial effects of physical exercise on cognition. This manuscript revised central ongoing research on epigenetic mechanisms induced by exercise and the beneficial effects on obesity-associated cognitive decline, highlighting potential mechanistic mediators.
Keywords: BDNF; Cognitive impairment; Epigenetics; Exercise; Gene expression; Obesity